The Usefulness of Soluble ST2 Concentration in Heart Failure with Reduced Ejection Fraction to Predict Severe Impairment in Exercise Capacity Assessed in Cardiopulmonary Exercise Testing - Magdalena Dudek; Marta Kałużna-Oleksy; Filip Sawczak; Agata Kukfisz; Aleksandra Soloch; Jacek Migaj; Maciej Lesiak; Ewa Straburzyńska-Migaj (Biomedicines)
Background/Objectives: Heart failure (HF) constitutes a complex clinical syndrome that is highly prevalent worldwide, comprises a serious prognosis, and results in a reduced quality of life. Exercise capacity is one of the most significant parameters involved in the prognosis in HF patients. Our objective was to evaluate the relationship between the selected cardiopulmonary exercise testing (CPET) parameters and the concentration of novel biomarker sST2 in a group of patients with heart failure with reduced ejection fraction (HFrEF). Methods: A group of 135 patients with HFrEF was enrolled in this prospective cohort study. Patients were in the stable phase of the disease in the prior 4 weeks and received optimal medical treatment. Clinical and biochemical parameters were investigated. All patients performed maximal CPET. Results: The mean (SD) concentration of sST2 was 45.5 ± 39.2 ng/mL. Based on the CPET results, the cut-off value (52.377 ng/mL) was established, optimal for the discrimination of relative peakVO2 < 12 mL/kg/min. Patients were divided into two groups according to sST2 cut-off values determined with an ROC curve (AUC 0.692, 95% CI: 0.567–0.816). The mean relative peakVO2 in patients with higher sST2 was 14.5 ± 4.6 mL/kg/min, while in the second group, it was 17.6 ± 5.2 (p = 0.002). In the sST2 ≥ 52.377 ng/mL group, 55.6% of patients achieved VO2 < 50%. Subjects with lower sST2 values obtained higher values of PETCO2 (p < 0.001) and higher values of pulse O2 (p = 0.01). VE/VCO2slope (p = 0.002) was higher in patients with increased sST2 concentration. Conclusions: The concentration of sST2 protein is substantially associated with the clinical severity of heart failure with reduced left ventricular ejection fraction assessed by functional capacity through CPET.